Analysis and design for reducing residual stress and distortion after ejection of injection molded part with metal-insert - Jin, Kai; Jeong, Taesan; Kim, Taesan; Kim, Naksoo; Kim, Byeonggon (International journal of precision engineering and manufacturing, 2014)
With the rapid development of injection molded parts in different fields, products such as injection molded part with metal-insert are usually requested to have high precision and complicated shape. During producing process, residual stresses and deformations such as warping, local bending and shrinkage are produced due to temperature change, pressure and cooling regime during packing and cooling stages. In this research, numerical analysis of residual stress generated during the packing and cooling stages of injection molding process was carried out. And the magnitude and distribution of final distortions were predicted, which were consistent with experimental measurement. So we came to the conclusion that the residual stresses were formed due to different temperature gradient, causing thermal stresses become uneven distribution. After ejection, the uneven residual stress caused local distortion. Furthermore, the residual stresses were formed due to the process parameters. Besides finding the reason of distortion, another task was to minimize the distortion. So that optimal design was taken to design important parameters such as melt temperature, die temperature, packing pressure and packing time. The results by optimal design showed that it could reduce the deformation of product effectively.